2019
DOI: 10.2147/jpr.s209610
|View full text |Cite
|
Sign up to set email alerts
|

<p>Mesotherapy in the treatment of musculoskeletal pain in rehabilitation: the state of the art</p>

Abstract: Background Mesotherapy can be included as an ancillary treatment in the management of localized pain in rehabilitation, but there are no definitive treatment protocols for this approach. Objectives The purpose of this review was to examine new indications for more standard protocols of mesotherapy in rehabilitation. Materials and methods This systematic review was performed using the following resources: PubMed, Cochrane, PEDro, Scopus, and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 48 publications
(72 reference statements)
0
33
0
Order By: Relevance
“…Many previous studies of MT were conducted on chronic neck pain, comparing the effect of MT with local anesthetic lidocaine hydrochloride vs dry mesotherapy for 3 sessions showing reduction of pain on VAS scale by the 12th week of the study [47], as well as acute neck pain comparing single injection MT with local anesthetic and steroids vs oral ibuprofen, which showed more analgesic effect than ibuprofen taken orally [48]. Studies on acute back pain (using sterile water microinjections) [49], and in female patients with chronic back pain during labor [50], showed a reduction of pain using VAS score; moreover, studies for chronic spinal pain using weekly MT injection (normal saline, lidocaine 2% and lysine acetylsalicylate) for 5 weeks showed improved pain and functional outcome [51]; also, in the result of a randomized controlled study of 84 patients with low back pain study using mesotherapy of lidocaine, ketoprofen, and methylprednisolone for 5 sessions and follow-up after 6 months, they found the same effect as systemic drugs given to the control group ( ketoprofen, methylprednisolone, and esomeprazole) [11]. A recent study for knee osteoarthritis showed improvement of pain and functional outcome after 3 months' follow-up reported by Chen et al [52] comparing the effect of oral diclofenac 150 mg/day to MT (2 ml lidocaine, 40 mg piroxicam, and 100 units of calcitonin) for acute knee pain and second protocol of MT (2 ml lidocaine, 2 ml organic silica, and 100 units calcitonin) for chronic knee pain, where they concluded that MT is a safe and effective procedure to decrease pain [53].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Many previous studies of MT were conducted on chronic neck pain, comparing the effect of MT with local anesthetic lidocaine hydrochloride vs dry mesotherapy for 3 sessions showing reduction of pain on VAS scale by the 12th week of the study [47], as well as acute neck pain comparing single injection MT with local anesthetic and steroids vs oral ibuprofen, which showed more analgesic effect than ibuprofen taken orally [48]. Studies on acute back pain (using sterile water microinjections) [49], and in female patients with chronic back pain during labor [50], showed a reduction of pain using VAS score; moreover, studies for chronic spinal pain using weekly MT injection (normal saline, lidocaine 2% and lysine acetylsalicylate) for 5 weeks showed improved pain and functional outcome [51]; also, in the result of a randomized controlled study of 84 patients with low back pain study using mesotherapy of lidocaine, ketoprofen, and methylprednisolone for 5 sessions and follow-up after 6 months, they found the same effect as systemic drugs given to the control group ( ketoprofen, methylprednisolone, and esomeprazole) [11]. A recent study for knee osteoarthritis showed improvement of pain and functional outcome after 3 months' follow-up reported by Chen et al [52] comparing the effect of oral diclofenac 150 mg/day to MT (2 ml lidocaine, 40 mg piroxicam, and 100 units of calcitonin) for acute knee pain and second protocol of MT (2 ml lidocaine, 2 ml organic silica, and 100 units calcitonin) for chronic knee pain, where they concluded that MT is a safe and effective procedure to decrease pain [53].…”
Section: Discussionmentioning
confidence: 85%
“…Our designed protocol for treating Achilles tendinopathy with MT was not yet typical to other protocols, but of similar drugs used before and in similarity to the conclusions of recent review done by Paolucci et al [11] where they stated that MT is a good option for pain management, using microinjections either superficial or profound intradermal infusion in the painful area or the trigger points with the specific needle and number and correct dosage of the used drugs, with average sessions ranging from single to 9 sessions and the most used drugs are lidocaine, sterile water, isotonic saline, vitamin B solutions, long-acting corticosteroids, acetylsalicylate, ketorolac, and botulinum toxin. In our results, the glucocorticoids injected group showed decreased inflammation signs by the 12th week follow-up documented ultrasonographically as decreased Doppler signs.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, the available studies do not allow a standardization of this technique due to the different research methods. Significant clinical benefits such as pain control, improvement of quality of life, systemic dose 2 e Scientific World Journal reduction, and patient satisfaction were reported [7,12,13].…”
Section: Analgesic Mechanism Of Actionmentioning
confidence: 99%
“…Intradermal therapy can also synergize with other therapeutic strategies, for example, to reduce dose of systemic opioid [35] or to improve the effects of rehabilitation, in combination with ultrasound [36] or antalgic electrotherapy [37,38]. It has a remarkable success even in patients undergoing rehabilitation programs for musculoskeletal disease [13] or after sports trauma [7]. Although laser and intradermal therapy have different frequency, it may be useful to consider a combination of these two therapies.…”
Section: Combination With Other Therapiesmentioning
confidence: 99%